Multifactor dimensionality reduction analysis of MTHFR, PAI-1, ACE, PON1, and eNOS gene polymorphisms in patients with early onset coronary artery disease - GÜNEY, AHMET İLTER (SAGE PUBLICATIONS LTD, 2011)
Background: Association studies in the Turkish population have investigated the single locus effects of different gene polymorphisms on coronary artery disease (CAD). CAD is a complex polygenic disease that involves complex interactions among multiple genetic and environmental conditions. Design: We evaluated associations of five candidate genetic polymorphisms (methylene tetrahydrofolate reductase C677T, plasminogen activator inhibitor 4G/5G, endothelial nitric oxide synthase (eNOS) 3-27 base pair repeat, insertion, or deletion of a 287 bp Alu repeat sequence polymorhism of angiotensin I converting enzyme, and paraoxonase Gln192Arg PON1 polymorphisms) with the presence and extent of early onset CAD. Methods: DNA was isolated and amplified from 90 consecutive patients with angiographically proven early onset CAD (ages 41 +/- 5 for men, 49 +/- 7 for women) and also from 90 control subjects with no significant coronary obstruction angiographically (ages 42 +/- 5 for men, 48 +/- 6 for women). Multifactor dimensionality reduction (MDR) analysis was performed to identify a model of CAD based on both genetic and conventional risk factors. Results: MDR analysis detected a significant model with four genes (prediction success similar to 61%, p = 0.03). When the total number of the conventional risk factors is analysed with the candidate polymorphisms, a different model is identified that includes three of the four genes from the above model and achieves a similar prediction of CAD as the gene only model. Conclusion: These data indicate that gene-gene and gene-environmental risk interactions form significant models in predicting early onset CAD.
Keywords: ACE I/D; coronary artery disease; eNOS 3-27; Gln192Arg PON1; MTHFR C677T; multifactor dimensionality reduction; PAI-1 4G/5G; EPISTASIS